Liberalizaç\~ao financeira, performance e econômica e estabilidade macroeconômica no Brasil: Uma avaliaç\~ao do período recente - Jo\~ao Adelino de Faria; Luiz Fernando de Paula; Manoel Carlos de Castro Pires; Tiago Rinaldi Meyer (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper aims at analyzing the relationship between capital account liberalization,economic performance and macroeconomic stability in Brazil. For this purpose,besides a revision in the literature, the paper develops an empirical study on the effects of financial liberalization in Brazil on a set of macroeconomic variables usingtwo models: one with a de jure index of financial liberalization, and another with a defacto index of financial integration. In the first model, the study intends to evaluatethe proposal that the full convertibility of capital account in Brazil would result in the reduction of country-risk and, consequently, of the domestic interest rate. In the second one, it aims at assessing the hypothesis that financial liberalization has positive effect on economic growth and macroeconomic stability vis-à-vis the hypothesis of the critics of financial liberalization that support that it generates unstable effects on developing economies.
Keywords: E32; F32; F43; 330; Kapitalbilanz; Kapitalverkehrskontrolle; Finanzmarktregulierung; Brasilien